SAT0035 The effects of visfatin, resistin and il-17 on synovial fibroblasts from different rheumatic disease backgrounds. (12th June 2018) - Frommer, K.; Rehart, S.; Sauerbier, M.; Müller-Ladner, U.; Neumann, E.
Abstract : Background: Although rheumatoid arthritis (RA) and psoriatic arthritis (PsA) have several features in common, they also possess distinct differences. We hypothesised that RA and PsA synovial fibroblasts (SF), known key effector cells in the pathophysiology of inflammatory arthritis, differentially respond to various stimuli including adipokines and cytokines and that this may contribute to those differences. For example, IL-17 (also found in synovial tissue) is of particular therapeutic significance in PsA but not as effective in RA. Thus far, IL-17 in its isoform IL-17A has been the major therapeutic target in PsA but IL-17F also plays a role in the IL-23/IL-17 axis of inflammatory diseases. Objectives: Therefore, we analysed the responses of SF from patients with PsA, RA or no rheumatic disease to IL-17A/F±TNF-α and the adipokines visfatin and resistin, which show strong expression in the synovium of inflammatory arthritis. Methods: SF were isolated from patients with PsA, RA or non-rheumatic disease controls (N), each undergoing joint surgery. PsASF, RASF and NSF were stimulated with human recombinant IL-17A/F, TNF-α, visfatin, and resistin. A neutralising anti-IL-17A antibody was used to verify specificity of the IL-17A effects. Secretion of the proinflammatory cytokine IL-6 was used as the initial readout parameter and was quantified using a commercial immunoassay. Results: Stimulation with visfatin caused a strong increase in IL-6 secretion in all SF types (n=3 each), while resistin had no effect. Differences in responses were not statistically significant between the SF types studied. IL-17A at concentrations found in serum or synovial fluid did not induce IL-6 secretion in any of the SF. Dose-response curve analysis showed that considerably higher concentrations of IL–17A, which may occur locally in tissue, are required for the induction of IL-6 secretion. An anti-IL–17A antibody abolished the effect, thus showing that the effect is specific for IL-17A. The effects of IL-17A and IL–17F on IL-6 secretion by PsASF could be strongly amplified by a co–stimulation with TNF-a (IL-17A: 5-fold vs 113-fold; IL-17F: 1.7-fold vs 39-fold; TNF-α alone: 12-fold). The effects were stronger for IL-17A than for IL–17F with or without TNF co–stimulation. No effect of IL–17F alone was observed on NSF (n=1). Conclusions: SF from RA and PsA patients were not differentially affected by the adipokines visfatin and resistin or IL-17A when used at serum or synovial fluid concentrations suggesting inflammatory cells to be the primary target of anti-IL-17 therapy. In its use as a therapeutic target, the attribute of IL-17F affecting PsASF would potentially increase the beneficial effects. Acknowledgements: This work was supported by an unrestricted educational grant from Celgene GmbH. Disclosure of Interest: K. Frommer Grant/research support from: unrestricted educational grant from Celgene GmbH, S. Rehart: None declared, M. Sauerbier: None declared, U. Müller-Ladner: None declared, E. Neumann: None declared